Mitigation mechanism of silicon and iron co-application to cadmium toxicity in tomato seedlings by integrated transcriptomic and physiological correlation analysis - Zhou, Xiaoting; Wang, Wenjie; Ye, Deyang; Liu, Xiaoru; Peng, Chutong; Tang, Yunxin; Su, Lihong; Cheng, Shaobo; Cao, Kai; Lei, Qiyuan; Pan, Tonghua; He, Zhongqun (Frontiers in Plant Science, 2025)
Cadmium (Cd) readily accumulates in plants during agricultural activities, leading to diminished crop yields and quality and posing a risk to humans. Silicon (Si) and iron (Fe) have shown promise in mitigating Cd toxicity, but the efficacy of their combined application to alleviate the stress of Cd remains unclear. This study focused on the physiological and transcriptomic responses of tomato seedlings to Cd stress. When tomato seedlings were subjected to Cd stress, the application of external Si and Fe effectively alleviated Cd toxicity; increased photosynthetic pigment content, antioxidant enzyme activity, and transcription factor; and improved plant growth. Transcriptome analyses revealed that photosynthetic antenna proteins, photosynthesis-related processes, and glutathione metabolism were significantly overrepresented among differentially expressed genes when plants were subjected to Si-Fe competition under Cd stress conditions. Fructose-bisphosphate aldolase is a critical component in the mechanism of the effectiveness of Si-Fe in mitigating Cd toxicity. The hub genes CAB13 and CAB6A could potentially play a role in the modulation of photorespiration and light-capture processes when subjected to Si-Fe treatment. These findings offer novel insights into the environmental impacts and underlying mechanisms governing the roles of Si and Fe in reducing Cd toxicity.